Unification of New Zealand's local vertical datums: iterative gravimetric quasigeoid computations - Featherstone, Will; Amos, Matthew (Springer - Verlag, 2009)
New Zealand uses 13 separate local vertical datums (LVDs) based on normal-orthometric-corrected precise geodetic levelling from 12 different tide-gauges. We describe their unification using a regional gravimetric quasigeoid model and GPS-levelling data on each LVD. A novel application of iterative quasigeoid computation is used, where the LVD offsets computed from earlier models are used to apply additional gravity reductions from each LVD to that model. The solution converges after only three iterations yielding LVD offsets ranging from 0.24 m to 0.58 m with an average standard deviation of 0.08 m. The so-computed LVD offsets agree, within expected data errors, with geodetically levelled height differences at common benchmarks between adjacent LVDs. This shows that iterated quasigeoid models do have a role in vertical datum unification.